2017
DOI: 10.1128/jvi.01240-17
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Exploits a Dynamic Multi-aminoacyl-tRNA Synthetase Complex To Enhance Viral Replication

Abstract: A hallmark of retroviruses such as human immunodeficiency virus type 1 (HIV-1) is reverse transcription of genomic RNA to DNA, a process that is primed by cellular tRNAs. HIV-1 recruits human tRNA Lys3 to serve as the reverse transcription primer via an interaction between lysyl-tRNA synthetase (LysRS) and the HIV-1 Gag polyprotein. LysRS is normally sequestered in a multi-aminoacyltRNA synthetase complex (MSC). Previous studies demonstrated that components of the MSC can be mobilized in response to certain ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 59 publications
1
68
0
Order By: Relevance
“…Strikingly, other ARSs were not detected in HIV-1, suggesting that KRS might be specifically incorporated into viral particles 89,93 . Recently, Duchon et al 94 observed that HIV-1 infection triggered the release of KRS from the MSC to form a free pool of KRS, which might be due to the specific phosphorylation of S207 in KRS ( Fig. 3a).…”
Section: Arss and Infectious Diseases Arss In Virus Infectionmentioning
confidence: 93%
“…Strikingly, other ARSs were not detected in HIV-1, suggesting that KRS might be specifically incorporated into viral particles 89,93 . Recently, Duchon et al 94 observed that HIV-1 infection triggered the release of KRS from the MSC to form a free pool of KRS, which might be due to the specific phosphorylation of S207 in KRS ( Fig. 3a).…”
Section: Arss and Infectious Diseases Arss In Virus Infectionmentioning
confidence: 93%
“…Another study suggested that HIV-1 uses host mitochondrial KRS during the packaging process [74]. Because KRS is normally associated with the MSC, HIV-1 could exploit the dynamic nature of the MSC to redirect and co-opt cellular translation factors [75]. Indeed, HIV-1 infection triggers release of KRS from the MSC, possibly through phosphorylation at Ser207 [75].…”
Section: Communication Between the Mammalian Ars System And Virusesmentioning
confidence: 99%
“…Because KRS is normally associated with the MSC, HIV-1 could exploit the dynamic nature of the MSC to redirect and co-opt cellular translation factors [75]. Indeed, HIV-1 infection triggers release of KRS from the MSC, possibly through phosphorylation at Ser207 [75]. This PTM is important for KRS packaging into virions and progeny virus infectivity [75].…”
Section: Communication Between the Mammalian Ars System And Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSC serves as a reservoir for ARSs with noncanonical functions, as well as facilitating tRNA channeling and translation (61). Interestingly, HIV-1 infection leads to an increased pool of non-MSC-associated ARSs (62).…”
Section: Aminoacyl-trna Synthetases As Regulatory Factors In Rt Primementioning
confidence: 99%